IbM Millenial Cerdas Keuangan bagi Siswa SMKN 1 di Kabupaten Aceh Timur - Jamil, Muhammad; Jamali; Teuku Muana Refi; Erni Wiriani; Aziz, Abdul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
The purpose of this activity is to train students to understand the principles as well as financial planning and management. The hope is that students can be responsible for their pocket money, be able to control themselves, and don't prioritize unimportant needs. In addition, students can also understand the concept of a simple business recording system as the simplest and most efficient business financial recording technique for small business plans. Through this training, participants are expected to be able to apply and develop it. The method of implementing service activities consists of 3 stages, namely; 1) Observation, 2) Seminar and Training, and 3) Evaluation and Reflection. This Community Service Implementation Activity was carried out from early January 2020 to March 2020. 1. The results of this community service activity showed that the students looked very enthusiastic in following the material provided by the instructors, where the students had a great curiosity. For each material provided, the training provided is very helpful for students in understanding simple bookkeeping and financial records, as well as the establishment of partnerships and collaborations between the Nusantara Banking Finance Academy, East Aceh Regency, and SMKN 1 Idi, East Aceh Regency.